Understanding the markets - Loader, David; Securities Institute (Oxford : Butterworth-Heinemann, 2002)
An analysis of the major securities, derivatives and money markets from an operations point of view, 'Understanding the Markets' takes the reader through the major features and characteristics of the markets and the products. The relationship between the trading and dealing functions and the operations functions is examined and the issues discussed. This book looks at the financial markets from the viewpoint of the person working in the operations functions that support the trading, dealing and investment processes, and as such is essential reading in order to fully understand the industry, an industry which has gone, and is still going through, much change.
Knowing how the markets work and what impacts on the operations team is crucial for managers and supervisors. In this book the author provides a full explanation of the markets and their impact in operations terms.
&#x000A
Includes index.
oif 21/07/14
Loan
Keywords: Financial services industry; Securities industry; Capital market